Current Trends in the Study of Rabbinic Judaism and its Relation to the New Testament - Delgado Gómez, Alfredo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
The use of rabbinic texts as a tool to better understand the context in which early Christianity emerged has a long history which continues in recent publications. The epochal shift in the study of rabbinic texts brought about by Neusner resulted in the questioning of their reliability for reconstructing the beginning of rabbinic Judaism. However, recent advances in research on rabbinic Judaism fail to permeate many N. T. scholars, who continue to use these texts uncritically, giving rise to erroneous views of Second Temple Judaism, the Pharisees and rabbinic Judaism. This study updates the state of research on rabbinic Judaism and raises considerations for use in the study of the N. T.
Keywords: Rabbinic Judaism; pharisees; Mishnah; Yabneh; Tosefta